Diet and plasma cholesterol in dairy cows - Saarinen, Pellervo (Agricultural and Food Science, 1955)
When the results of 12 feeding trials conducted with a total of 141 Ayrshire cows were analyzed statistically the following results regarding the effects of diet on the plasma cholesterol content of dairy cows were obtained. The proportional amount of fat in the ration, the level of energy required and the digestible crude fiber in the ration have statistically shown a distinct positive influence upon the plasma cholesterol content. The statistical dependence of plasma cholesterol content on the level of digestible crude protein in the ration has varied according to the circumstances showing a positive correlation in cows in normal condition and negative correlation in case of well conditioned cows. A temporary energy overfeeding or slight underfeeding have not shown any distinct effect upon the plasma cholesterol content. An increase in the degree of fatness appeares to increase the level of cholesterol in blood plasma appreciably. The age of cows (2—13 years) apparently does not affect the level of plasma cholesterol. The results obtained with barren cows differ from those obtained with normal cows. The plasma cholesterol content can be used as a reliable indicator for several dietic factors which affect the liver functions but which are otherwise hard to establish.